Opportunities and Challenges of Indian Pharmaceutical Sector: An overview - , Dr.Shwetha G.S. 3, Umesh Chandra1, Dr. Sridharan S2 (International Journal of Scientific Research and Management (IJSRM), 2016)
The global pharmaceutical market size is estimated to reach USD 1.4 trillion and the Indian pharmaceutical market size is estimated as USD 55 billion by the year 2020. The Indian pharmaceutical sector is expected to grow with faster compound annual growth rate (CAGR) compared to global growth rate during the period 2015-2020. The world market will be dominated by countries like USA, EU and Japan and the contribution of Phrmerging countries is expected to be more in coming years. The future of the world pharmaceutical sector will be dominated by medicines for non communicable diseases and original branded medicines. The Indian pharmaceutical sector evolved in different phases from pre independence era to post Trade-Related Aspects of Intellectual Property Rights (TRIPS). Presently, Indian pharmaceutical sector is dominated by the generics drugs and more drugs are sold in anti-infective category. The Indian pharmaceutical industry is having opportunities in the domestic market with growing demand for quality health care. More opportunities are seen in the area of Contract Research and Manufacturing Services (CRAMS) by Mergers and Acquisitions (M&A) and Biogenic market. The government of India has taken measures to boost pharmaceutical sector, even though, the pharmaceutical sector is facing challenges in patent rights and methods used for fixing ceiling price for drugs. More challenges are expected due to immature clinical trial regulations and ethical aspects.